PANDANGAN IDDAH BAGI PEREMPUAN PASAL 170, BAB XIX DALAM KOMPILASI HUKUM ISLAM - Sumiati, Sumiati (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
This paper focuses on the description of the views of Iddah (mourning) of women who have been killed by those accounted for in the Compilation of Islamic Law (KHI) about the period of mourning with women (wives) who lived in the past, explained in article 170, Chapter XIX , Compilation of Islamic Law (KHI), first a wife who lives dead by her husband, is obliged to carry out a period of mourning during the iddah period as a substitute for grieving and at the same time resulting in slander. Both husband who lived in death by his wife, doing a period of mourning according to propriety.